Pravni vidiki položaja ciljne družbe glede skrbnega pregleda - Jovanovič, Dušan (Podjetje in delo, 2014)
The authors present the due diligence procedure in the target company. Further they focus on the question about the competent organ in the target company to allow the due diligence to be completed. The authors then continue with finding the answer to whether the due diligence is a right or a privilege of the buyer. The article is concluded by examining the extent to which the competent organ of the target company is righteous to deliver information and documentation about the company.
Keywords: gospodarske družbe; podjetja; prevzem; vodenje